Cost-Effectiveness Analysis of the Prophylactic Use of Ertapenem for the Prevention of Surgical Site Infections after Elective Colorectal Surgery - Costanza Vicentini; Maria Michela Gianino; Alessio Corradi; Noemi Marengo; Valerio Bordino; Silvia Corcione; Francesco Giuseppe De Rosa; Giovanni Fattore; Carla Maria Zotti (MDPI AG, 2021)
Standard surgical antimicrobial prophylaxis (SAP) regimens are less effective in preventing surgical site infections (SSIs) due to rising antimicrobial resistance (AMR) rates, particularly for patients undergoing colorectal surgery. This study aimed to evaluate whether ertapenem should be a preferred strategy for the prevention of SSIs following elective colorectal surgery compared to three standard SAP regimens: amoxicillin-clavulanate, cefoxitin, and cefazolin plus metronidazole. A cost-effectiveness analysis was conducted using decision tree models. Probabilities of SSIs and AMR-SSIs, costs, and effects (in terms of quality-adjusted life-years) were considered in the assessment of the alternative strategies. Input parameters integrated real data from the Italian surveillance system for SSIs with data from the published literature. A sensitivity analysis was conducted to assess the potential impact of the decreasing efficacy of standard SAP regimens in preventing SSIs. According to our models, ertapenem was the most cost-effective strategy only when compared to amoxicillin-clavulanate, but it did not prove to be superior to cefoxitin and cefazolin plus metronidazole. The sensitivity analysis found ertapenem would be the most cost-effective strategy compared to these agents if their failure rate was more than doubled. The findings of this study suggest ertapenem should not be a preferred strategy for SAP in elective colorectal surgery.